Have monetary data releases helped markets to predict the interest rate decisions of the European Central Bank? - Alexander Jung (European Central Bank (ECB), 2016)
This paper examines whether monetary data releases by the European Central Bank (ECB) have provided markets with additional clues about the future course of its monetary policy. It conducts a novel econometric approach based on a combination of an Ordered Probit model explaining future policy rate changes (sample 2000 to 2014) and the Vuong test for model selection. Overall, our results suggest that information contained in press releases on monetary developments for the euro area has helped markets in forming their expectations on the next monetary policy decision.
Keywords: C34; D78; E52; E58; 330; communication; monetary analysis; predictability; Probit model; Vuong test